Autism and Trans Identity - Moore, Felix (Murmurations: Journal of Transformative Systemic Practice, 2022)
Much discussion of the documented link between autism and transgender identity focuses on identifying a reason behind this link, with the implication that if a cause were to be identified, this would justify disregarding or questioning the trans identity of autistic people to a greater extent than is already the case. I focus instead on the commonalities between the trans and autistic experiences, including pathologisation, medical gatekeeping and a lack of representation in public discourse about both autism and trans identity, which tend to be dominated by non-autistic and cisgender people respectively.